Understanding of maslaha and maqasid al-shariah concepts on Islamic banking operations in Malaysia - Awang, Mohd Daud; Asutay, Mehmet; Jusoh, Mohd Kamal Azman (Department of Syariah, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2014)
Since the 50's, Malaysia has taken the lead in the role of studies on Islamic Banking and Financial System (IBFS). Malaysia has successfully introduced a variety of IBFS products and services and thus is recognised globally as a front-liner of the Islamic banking and finance industry. Nevertheless, world recognition and past success do not stop the industry from facing new challenges and issues. Many Islamic scholars continue to work on their research in IBFS for innovation to fulfil the Muslims’ needs for Shariah-compliant products and services. This in turn, requires a thorough understanding of the Islamic jurisprudence methods. However, some researchers argued that Maslaha and al-Maqasid, in the recent financial issues have shown that there might be negative implications on individuals such as bankruptcy and family financial problems based on some Islamic debt products and services. From an economic stand, if the issues worsen, this could lead to a crisis. Relating these indications to the proactive debt financing, it is found to contradict the Maqasid al-Shariah. Therefore it is crucial to understand the depth of all aspects that utilise Maslaha and al-Maqasid concepts as reference. This paper explores and identifies the concepts of Maslaha and Maqasid al-Shariah in Islamic banking operations with a holistic understanding. The research also includes a critical analysis on the issues of uses of these methods as a systematic jurisprudence. At the end of the paper, some suggestions are provided on ways to improve the development of IFS in Malaysia in order to make the IBFS more resilient and competitive through the understanding of Maslaha and Maqasid al-Shariah for the well-being of the users.